Unmasking the expert deceiver: grounded theory analysis of long-term, high-stakes deception expertise development - Bertrand, Heather, author; Merolla, Andrew, advisor; Unnithan, N. Prabha, 1952-, committee member; Anderson, Karrin Vasby, committee member (Colorado State University. Libraries, 2010)
The current study attempted to garner knowledge about expert deceivers by analyzing personal accounts of their deceptive behaviors. The goal was to understand the methods these individuals employed to become master deceivers. A selection of 12 autobiographical texts describing the exploits of three types of expert deceivers (i.e., confidence artists, espionage agents, and undercover law enforcement agents) were analyzed using a categorizational system derived from previous grounded theory research. The results from the analysis led to the development of the deception skill model, which illustrates the complex relationship of processes that occur during the development and utilization of deception expertise. Knowledge gained from this study adds to the existent body of deception research along with, potentially, adding a new avenue of deception research and practical applications for deception detectors.
Department Head: Sue Pendell.